Pengaruh penambahan karbon aktif terhadap parameter pertumbuhan dan kelangsungan hidup ikan nila (oreochromis niloticus) dalam wadah terkontrol - Iroth, Revelino A.; Mokolensang, Jeffrie F.; Pangemanan, Novie P.L.; Lantu, Sartje; Pangkey, Henneke; Sondakh, Calvyn F.A. (e-Journal BUDIDAYA PERAIRAN, 2019)
The Aim of this study was to determine the effect of additional activated carbon in fish feed with different composition for the growth performance of Nile (Oreochromis niloticus), include feed efficiency (FE), specific growth rate (SGR) and feed conversion ration (FCR). This research was carried out indoor Laboratory. The test container used was an aquarium measuring 60 x 40 x 40 cm placed in a laboratory. The experimental research design method used was a completely randomized design (ANOVA) with 5 treatments and 3 replicates. The treatments used were A: Control, B: 1%, C: 2%, D: 3%, E: 4%. The results of statistical analysis on the growth variables showed the same effect on the growth of tilapia. The best weigth gain on growth performance occurred in treatment D (4.49), fish feeding with pellet charcoal composition of 3%, as well as relative growth (101.4), and daily growth (2.32%). The results of the statistical analysis of the effect of treatment on the value of efficiency provide a very real effect. The highest value of feed conversion occurred in treatment C (1.05), namely the feeding of pellets with charcoal composition of 2%, and the lowest treatment B (1.86). This study can be concluded that the administration of 1%, 2%, 3%, 4% charcoal and without charcoal is the same effect in triggering the growth of 3-5 cm tilapia.